STRATEGIC PLANNING AND FORECASTING IN THE TOURISM INDUSTRY - R. V. Gavva; E. N. Lozhkomoeva (Вестник университета)
The article considers the essence and role of strategic planning in the activities of organizations of the tourism industry. The paper shows that the concept of the life cycle of tourist services can serve as a justification for strategic management decisions. The authors formulate the main approaches to the study of the life cycle of tourist services. The study determines the directions of using information at different stages of the life cycle of services in the field of tourism. The article proposes approaches to the operational definition of the type of service and the stage of its life cycle, which contributes to the adoption of sound strategic management decisions that ensure the effective, stable operation of tourist organizations. The paper determines that the modern development of the tourism market should be based on a combination of regional, Federal, national, and international tourism policies that combine strategic planning with the tasks and needs of the short-term perspective.